Pengaruh Teknik Pembelajaran Brain Breaks Terhadap Hasil Belajar Siswa Kelas IV pada Materi Hak dan Kewajiban Fase B SDIT Insan Madani Kota Palopo - Nurazizah; Nurdin K; Ervi Rahmadani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the issue of suboptimal student learning outcomes. In the learning process, student learning outcomes can vary, making it necessary to implement learning strategies that can help improve these outcomes. Therefore, this study aims to examine the implementation of the Brain Breaks learning technique, the differences in student learning outcomes before and after the implementation of this technique, and the effect of the Brain Breaks learning technique on student learning outcomes. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The study was conducted at SDIT Insan Madani in Palopo City from October to November 2025 with a sample of 26 fourth-grade students. Data collection was carried out through tests in the form of pretests and posttests as well as questionnaires. The data obtained were then analyzed using a statistical test, namely the paired sample t-test. The results of the study indicate an improvement in student learning outcomes, with the average pretest score of 64.88 increasing to 86.92 on the posttest. The results of the paired sample t-test showed a significance level of p < 0.001, indicating a highly significant effect of the Brain Breaks learning technique on the learning outcomes of fourth-grade students regarding the rights and obligations phase B material at SDIT Insan Madani in Palopo City. Thus, the Brain Breaks learning technique can be used as an effective learning strategy to improve student learning outcomes